2018
DOI: 10.7554/elife.31257
|View full text |Cite|
|
Sign up to set email alerts
|

MERS-CoV spillover at the camel-human interface

Abstract: Middle East respiratory syndrome coronavirus (MERS-CoV) is a zoonotic virus from camels causing significant mortality and morbidity in humans in the Arabian Peninsula. The epidemiology of the virus remains poorly understood, and while case-based and seroepidemiological studies have been employed extensively throughout the epidemic, viral sequence data have not been utilised to their full potential. Here, we use existing MERS-CoV sequence data to explore its phylodynamics in two of its known major hosts, humans… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
187
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(204 citation statements)
references
References 99 publications
14
187
1
2
Order By: Relevance
“…A retrospective study 27 29 In 2014, the nosocomial outbreaks in Abu Dhabi, United Arab Emirates, 50 were due to the spread of MERS-CoV in health-care settings, predominantly occurring well before MERS-CoV infections were recognised and diagnosed. The rapid spread was attributed to poor compliance among health-care workers with wearing personal protection equipment while interacting with patients and application of AGPs, including intubation, manual ventilation before intubation, nebulised medications, and oxygen therapy.…”
Section: Nosocomial Transmissionmentioning
confidence: 99%
“…A retrospective study 27 29 In 2014, the nosocomial outbreaks in Abu Dhabi, United Arab Emirates, 50 were due to the spread of MERS-CoV in health-care settings, predominantly occurring well before MERS-CoV infections were recognised and diagnosed. The rapid spread was attributed to poor compliance among health-care workers with wearing personal protection equipment while interacting with patients and application of AGPs, including intubation, manual ventilation before intubation, nebulised medications, and oxygen therapy.…”
Section: Nosocomial Transmissionmentioning
confidence: 99%
“…Additionally, the zoonotic introduction time and seasons play an important role in the disease spread. Based on the analysis of the distribution of human outbreak cluster size, it has also been demonstrated that the time of zoonotic introduction and season plays a significant role in human outbreak driven by MERS-CoV in Arabian Peninsula [22]. The MERS-CoV is known to have genetic diversity.…”
Section: Introductionmentioning
confidence: 99%
“…MERS-CoV is endemic in camels, the zoonotic reservoir host, with evidence of infection going back at least 30 years 2 . Camels in the Middle East and perhaps in East Africa continue to seed human infections which may require hospitalization especially in aged individuals with preexisting comorbidities 1,3,4 . Similar to severe acute respiratory syndrome CoV (SARS-CoV), MERS-CoV has spread to over 27 countries via air travel of infected people 5 .…”
mentioning
confidence: 99%